What Leads To Shared Attention? Maternal Cues and Infant Responses During Object Play. (23rd August 2017) - Deák, Gedeon O.; Krasno, Anna M.; Jasso, Hector; Triesch, Jochen
Abstract : Attention sharing provides an important context for infant learning, but it is not fully understood how infants respond to parents' isolated or combined actions to shift from nonsharing to attention‐sharing states. To investigate this, we recorded unscripted toy‐play interactions of infants (3 to 11 months old, N  =   35) and mothers at home, and coded attention‐related behaviors. These included infants' and mothers' visual fixations, and mothers' attention‐directing actions including gaze shifts, pointing gestures, object manipulations, verbalizations, and object sounds. In addition, dyadic attention was continuously classified into one of seven states of shared or nonshared attention. Results showed that mothers usually produced a combination of attention‐directing cues within the 7 sec. before infants shifted their attention to match the mother's focus. Mothers' cue combinations usually included object manipulation and either a gaze shift or a verbalization. Infants seldom looked at mothers' faces and followed a very small proportion of isolated gaze shifts or pointing gestures. However, infants frequently shifted attention to watch mothers manipulate objects. The results indicate that during toy play, combinations of maternal attention‐specifying actions selectively elicit infants' attention following.